ANALISIS QUICK RATIO PADA PT. INDOFOOD SUKSES MAKMUR TBK - Emiyati .; Wulandari .; Aris Munandar (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2020)
The development of the business world becomes increasingly competitive in the business world will be increasingly stringent. More and more new companies are emerging who are ready to compete with old companies, and therefore companies must be able to compete and pay off the short-term needs of the most liquid assets with the most liquid required by the company. This study is intended to determine the results of the company's needs in meeting the short and significant requirements by using the Quick ratio analysis at PT. Indofood success prosperous Tbk. By using the method of rapid ratio analysis and testing (one-sample test). Based on the results of the analysis of the product and Service Statistics (SPSS), which can be proven, the value of Tcount is 16,213 ˃ table 2,776. meaning H0 is rejected and Ha is accepted. With a significant level of 0.00 <0.05. Thus it can be concluded this study, the results of rapid ratio analysis at PT. Indofood Sukses Makmur Tbk. Period 2014 - 2018, the liquid is very good.